Pengaruh Emotional behavior dan motivasi kerja terhadap kinerja dengan Burnout sebagai mediasi (Studi Pada Frontliner di Coffeeshop Samarinda) - Anwar, Muhammad Hairil; indrawati, Andi; Nurfitriani, Nurfitriani (Jurnal Locus Penelitian dan Pengabdian, 2026)
The coffee shop industry in Indonesia has experienced rapid growth with intense competition, requiring frontliners to display positive emotional behavior in serving customers. However, high emotional demands can potentially cause burnout which may decrease employee performance. This study aims to analyze the effect of emotional behavior and work motivation on the performance of coffee shop frontliners in Samarinda City with burnout as a mediating variable. The research method uses a quantitative approach with convenience sampling technique, involving 30 coffee shop frontliner respondents in Samarinda. The research instrument consisted of a questionnaire with a 5-point Likert scale that has been tested for validity and reliability. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results show that emotional behavior and work motivation have no significant effect on frontliner performance or burnout. Conversely, burnout was proven to have a negative and significant effect on performance (significance 0.010), meaning that the higher the level of burnout, the lower the frontliner performance. The Sobel mediation test shows that burnout does not mediate the relationship between emotional behavior and performance or between work motivation and performance. This finding indicates that burnout acts as an independent variable that directly affects performance, not as an intervening variable. This study concludes that burnout is a key factor determining the quality of coffee shop frontliner performance, therefore coffee shop managers need to focus on burnout prevention and management strategies to maintain optimal service performance.